Antibacterial Activity of Extract and Ethanol-Water Fraction of White Pomegranate Peel (Punica granatum L.) Against Methicillin-resistant Staphylococcus aureus (MRSA) and TLC-Densitometry Test - Ningrum, Venita Lutfia; Wulansari, Endang Dwi; Franyoto, Yuvianti Dwi (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterial infection that is resistant to the antibiotic methicillin and the ?-lactam class of antibiotics. This study aims to determine the antibacterial activity of the extract and ethanol-water fraction of white pomegranate peel (Punica granatum L.) against MRSA bacteria and the TLC-Densitometry test. The results of this study are the antibacterial activity of the extract and the ethanol-water fraction at concentrations of 10%, 20%, and 30% were obtained: extract of 0,670 cm ± 0,010; 1,076 cm ± 0,010; 1,242 cm ± 0,010 and the ethanol-water fraction of 0,830 cm ± 0,010; 1,232cm ± 0,007; 1,419 cm ± 0,010. The gallic acid content in the extract was 3,13908 mg/ g sample and the ethanol-water fraction was 3,82457 mg/ g sample. The contents of phenolic compounds, tannins, and flavonoids can have the ability to inhibit MRSA bacteria, according to the results of a TLC bioautography test. Keywords: white pomegranate, Staphylococcus aureus, TLC bioautography, TLC-densitometry, fraction